Digigen and Communication Competency Analysis - Suci shinta lestari, (JIM - Journal International Multidisciplinary, 2023)
The talk active Digital Generation (DIGIGEN) phenomenon refers to the younger generation, especially Generation Z, who speak enthusiastically, are actively involved in conversations, and strive to interact effectively with the other person and grow and develop in the digital era which is full of technology and online connectivity. They are the generation most affected by digital technology, and the use of this technology has affected many aspects of their lives, including communication, education, entertainment and lifestyle. This research will describe the various competencies possessed by talk active DIGIGEN in an increasingly digitally connected environment. The depiction is based on the results of the Gen Z communication competency analysis displayed on Instagram social media. The research method used in this study is a qualitative descriptive research type. From the results of the analysis, there are 15 (fifteen) superior communication competencies possessed by Talk Active DIGIGEN in this digital era, namely: competence to communicate effectively by being an active listener, open oneself so that good cooperation and collaboration are established, empathize and understand others, be honest (authenticity) with personal data, competence adapt, competence digital awareness and responsible use of ICT, verify information sources, competence maintain online privacy and security, online ethics, leadership and have competence in maintaining digital balance.